2011
DOI: 10.4297/najms.2011.395
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic agents of otitis media in Benin city, Nigeria

Abstract: Background:Otitis Media continues to be a major presentation in the ear, nose and throat clinic.Aim:This study aimed to isolate, characterize and identify the bacteriological and mycological etiologic agents of otitis media in Benin city.Patients and Methods:Ear discharge from 569 (299 males and 270 females) patients diagnosed clinically of otitis media between August 2009 and August 2010 were processed to recover the bacterial and fungal etiologic agents. Susceptibility test was performed on all bacterial iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
25
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 15 publications
29
25
3
1
Order By: Relevance
“…Prakash et al 31 in their study isolated Coliforms including Klebsiella pneumoniae and Escherichia coli from 9.42% and 7.33% cases respectively, and these findings were similar to the reports by Mansoor et al 30 who reported the same to be 8% and 4% whereas Poorey and lyer et al 32 reported a highincidence for Klebsiella in their study (25.4% 27 and Osazuwa H el al 29 found fungal isolates in 12.25%, 15% and 8.8% cases of CSOM respectively against 5% cases in our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Prakash et al 31 in their study isolated Coliforms including Klebsiella pneumoniae and Escherichia coli from 9.42% and 7.33% cases respectively, and these findings were similar to the reports by Mansoor et al 30 who reported the same to be 8% and 4% whereas Poorey and lyer et al 32 reported a highincidence for Klebsiella in their study (25.4% 27 and Osazuwa H el al 29 found fungal isolates in 12.25%, 15% and 8.8% cases of CSOM respectively against 5% cases in our study.…”
Section: Discussionsupporting
confidence: 78%
“…as the second commonest. Kumar H et al 27 , Shymla R et al, 28 Osazuwa F et al 29 and Mansoor T et al 30 found Pseudomonas as the most prevalent organism in the isolates from the ear of the patients of CSOM.…”
Section: Discussionmentioning
confidence: 98%
“…All the identified bacterial isolates correspond to similar study done by Nwankwo and Okeke [13] who also reported the preponderance of S. aureus. In contrast however Osazuwa et al [12] and Ogbogu et al [15] reported Pseudomonas aeruginosa as the most frequent isolate of otitis media followed by S. aureus and Proteus spp. In developed countries, the commonest bacterial pathogens of acute otitis media were S. pneumoniae, H. influenzaeand M. catarrhalis [3] [5] [16].…”
Section: Discussionmentioning
confidence: 89%
“…Among Aspergillus species maximum strains isolated was Aspergillus fumigates 9(32.14%) followed by Aspergillus niger 4(14.29%). In a study from Nigeria on 569 patients of otitis media, fungi isolated were Aspergillus niger (9.2%) followed by Candida albicans (5.4%) [14]. In another study from India, fungal etiology was found in 15% of cases ,out of which 60% were Candida species and 40% were Aspergillus species [15].…”
Section: Discussionmentioning
confidence: 99%